Author Correction: Modern Anesthetic Ethers Demonstrate Quantum Interactions with Entangled Photons - Ryan K. Burdick; Juan P. Villabona-Monsalve; George A. Mashour; Theodore Goodson (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.